REFLEKSI PEMIKIRAN EKONOMI ISLAM ABU YUSUF - Kamilulloh, Farhan; Ridha, Sugantina; Aminuddin, Aminuddin; Ambardi, Prio (Islamic Banking & Economic Law Studies (I-BEST), 2023)
Most students today are more familiar with Adam Smith and other economic figures from the West, but we don't necessarily know that Islam also had early (classical) economic figures, such as al-Ghazali, Abu Ubaid and others. Therefore, it is interesting to discuss a brilliant Islamic economic figure of his time, namely Abu Yusuf. This research aims to reflect Abu Yusuf's thoughts. The method in this research uses the Research Library. The results of this research are the contribution of Abû Yûsuf's thoughts related to market mechanisms regarding demand and supply prices. Regarding taxation, Abu Yusuf advocates a tax system that is proportional, balanced and based on the principles of justice. In agricultural matters, to obtain greater production results by providing facilities for expanding agricultural land, and the costs are borne by the state.